2001
DOI: 10.1152/ajpgi.2001.281.3.g681
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation, not apoptosis, alters epithelial cell migration in small intestine of CFTR null mice

Abstract: Expression of a mutated cystic fibrosis transmembrane conductance regulator (CFTR) has been shown to enhance proliferation within CF airways, and cells expressing a mutated CFTR have been shown to be less susceptible to apoptosis. Because the CFTR is expressed in the epithelial cells lining the gastrointestinal tract and all CF mouse models are characterized by gastrointestinal obstruction, we hypothesized that CFTR null mice would have increased epithelial cell proliferation and reduced apoptosis within the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 26 publications
(25 reference statements)
8
47
0
Order By: Relevance
“…The intestinal tract of CF mice is known to exhibit a number of histological abnormalities, including goblet cell hyperplasia, accumulation of eosinophilic granules in the crypt lumen (5,24), and increased proliferation of crypt cells (18). Goblet cell hyperplasia in the villi was apparent in Cftr Ϫ/Ϫ Nhe3 ϩ/ϩ mice, as expected, but this phenotype was eliminated in CF mice …”
Section: Nhe3supporting
confidence: 60%
See 2 more Smart Citations
“…The intestinal tract of CF mice is known to exhibit a number of histological abnormalities, including goblet cell hyperplasia, accumulation of eosinophilic granules in the crypt lumen (5,24), and increased proliferation of crypt cells (18). Goblet cell hyperplasia in the villi was apparent in Cftr Ϫ/Ϫ Nhe3 ϩ/ϩ mice, as expected, but this phenotype was eliminated in CF mice …”
Section: Nhe3supporting
confidence: 60%
“…The effects of Nhe3 ablation on increased cell proliferation in the crypts of CF mice (18) were less clear. Nhe3-null mice exhibited an increase in cell proliferation that was similar in magnitude to that of CF mice, but when combined with the Cftr-null background the absence of both Nhe3 alleles appeared to have a moderating effect on this aspect of the phenotype.…”
Section: Surface the Effects Of Inhibitors Of Namentioning
confidence: 98%
See 1 more Smart Citation
“…An alkaline pH i in Cftr-deficient epithelium would negatively impact processes of apoptosis by diminishing cellular activity of acid endonucleases (5) and positively influence cell proliferation by facilitating G 2 /M transition in the cell cycle and enhancing membrane biogenesis (47,64). Previous studies (19) have shown that Cftr KO mice exhibit hyperproliferation of the intestinal epithelium, and it is known that cystic fibrosis patients have an approximately six-fold risk of gastrointestinal neoplasia despite being a relative young population (41). Thus the alkaline pH i in CF crypt epithelium may be a potential contributor to the propensity for gastrointestinal cancer in CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a potential link between CFTR and epithelial cell polarization has previously been proposed (Hollande et al, 1998) but the underlying mechanism remained unclear. In addition, increased proliferative activity was observed in intestinal crypt epithelial cells of CFTR-null mice (Gallagher and Gottlieb, 2001). The present work, together with these previous studies, indicates the possible role of CFTR in the control of proliferation and differentiation through modulation of the ZONAB pathway in several tissues.…”
Section: Discussionmentioning
confidence: 99%